CONCRETES WITH HIGH PERFORMANCE PROPERTIES FOR SPECIAL REPAIR WORK - Pshinko, O. M.; Rudenko, D. V.; Punahina, Yu. V. (Science and Transport Progress, 2006)
The article presents the results of experimental and theoretical research of the repair & restoration technologies at the special purpose structures. Experimental data have been provided for determining the strength of concrete, based on activated binder and matured in a sulfate medium. This confirms an essential improvement of operational performance of the concrete based on activated binder, used at repairs and reconstruction of the transport structures.